The disasters - England, M. K. (New York, NY : Harper, An Imprint of HarperCollins Publishers, 2018)
Nax and a handful of other space Academy washouts are the only surviving pilots after the school is hijacked by terrorists, but in order to spread the truth about the attack, Nax and his fellow failures must execute a dangerous heist.
Keywords: Science fiction